2003
DOI: 10.1034/j.1600-051x.2003.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of body composition and periodontal disease using nutritional assessment techniques: Third National Health and Nutrition Examination Survey (NHANES III)

Abstract: This study, indicating significant correlations between body composition and periodontal disease (with WHR being the most significant, followed by BMI, FFM, and S), showed similarities to those observed in other obesity-related health problems. This strengthened arguments that periodontal disease and certain obesity-related systemic illnesses are related, with abnormal fat metabolism possibly being an important factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
181
6
14

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 228 publications
(221 citation statements)
references
References 49 publications
20
181
6
14
Order By: Relevance
“…Nishida et al 27) suggested that obesity was second only to smoking as the predominant risk factor for inflammatory periodontal destruction of tissue. The results of other cross-sectional studies 1,8,15,22,36,37,43) also indicate an association between obesity and periodontal disease. The biological mechanisms for an association between obesity and periodontitis remain to be clarified.…”
Section: Discussionsupporting
confidence: 54%
“…Nishida et al 27) suggested that obesity was second only to smoking as the predominant risk factor for inflammatory periodontal destruction of tissue. The results of other cross-sectional studies 1,8,15,22,36,37,43) also indicate an association between obesity and periodontal disease. The biological mechanisms for an association between obesity and periodontitis remain to be clarified.…”
Section: Discussionsupporting
confidence: 54%
“…WC measurement was carried out using a measurement tape with a 1 cm variation at the umbilical scar, and measures of WC ≥102 cm for men and ≥88 cm for women suggested obesity (25). Hip circumference measures were also taken using the same measurement tape, and these measures were used to calculate the WHR (26). Patients were considered obese if WHR was ≥0.85 for women and ≥0.9 for men (22).…”
Section: Anthropometric Parametersmentioning
confidence: 99%
“…Significant correlations between body shape and periodontal disease demonstrated similarities to those observed in other obesityrelated health problems [42]. Translation of the currently obtained data on animal model to human organism should allow to consider dietary and probiotic tissues [44][45][46], probiotic strain impacts on pancreatic function, and insulin resistance for personalized dietology.…”
Section: Diet and Probioticsmentioning
confidence: 94%